EMPOWERING MICRO-ENTERPRISES WITH AN INTEREST-FREE LOAN: A CASE STUDY OF LAZISMU SURABAYA - Danastri Nisita Alyani; R. Moh. Qudsi Fauzi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
MSMEs have an important role in the growth of Indonesian economy. However, one of the obstacles that MSMEs have to face’s the lack of capital, MSMEs can’t develop if they don’t have capital. Capital can be provided by banks but not all MSMEs can apply for a loan from banks because of certain conditions. In this case, non-bank financial institutions can take over, including zakat institutions. LAZISMU Surabaya is one of zakat institution under authority of Muhammadiyah, which the object of research, has a program called Bina Mandiri Wirausaha (BMW) that fostering about 100 MSMEs owners. The purpose of this research is to determine the role of interest-free loans programmed by LAZISMU Surabaya, in order to answer the research gap that all informants are empowered after receiving an interest-free loan. This study used a qualitative descriptive method by utilizing in-depth interviews with 12 informants consisting of MSME owners and an administrator of LAZISMU Surabaya. Indicators of empowerment in this study are capital, income, sales volume, independence, religiosity, and the ability to give alms. If all indicators are fulfilled by MSME owners, it can be concluded that the role of LAZISMU Surabaya in empowering MSMEs is successful. The finding of this research shows that LAZISMU Surabaya has succeeded in empowering MSMEs.Keywords: Empowerment, MSMEs, LAZISMU, Zakat Infaq and ShadaqahREFFERENCE Kementerian Koperasi dan UMKM. (2020). Teten target lima tahun ke depan sebanyak 48.000 usaha kecil naik kelas. Jakarta: Kementerian Koperasi dan UMKM Republik Indonesia. Diakses dari http://www.depkop.go.id/ Pricewaterhouse Coopers Indonesia. (2019). Survei PwC: 74% UMKM belum dapat akses pembiayaan. Jakarta: Pricewaterhouse Coopers Indonesia. Diakses dari https://www.pwc.com/Republik Indonesia. (2008). Undang-Undang Republik Indonesia No. 20 Tahun 2008 Tentang Usaha Mikro, Kecil, dan Menengah. Diakses dari https://www.bi.go.id/ Kementerian Perdagangan. (2013). Analisis peran lembaga pembiayaan dalam pengembangan UMKM. Jakarta: Kementerian Perdagangan Republik Indonesia. http://bppp.kemendag.go.id/Winarni, Endang Sri. (2006). Strategi pengembangan usaha kecil melalui peningkatan aksesibilitas kredit perbankan.Ali, Zainuddin. (2008). Hukum perbankan syariah. Jakarta: Sinar Grafika.Azis, Harry Azhar. (2017). Zakat & pemberdayaan. Surabaya: Airlangga University Press.Kementerian Agama. (2019). Implementasi Sifat Ta'awun dalam lembaga keuangan syariah melalui akad al –qardh. Jakarta: Kementerian Agama Republik Indonesia. Diakses dari https://moraref.kemenag.go.id/Sudarsono, Heri. (2008). Bank & lembaga keuangan syari’ah. Yogyakarta: Ekonisia.Damanik, Janianton et al. (2018). Membangun pariwisata dari bawah. Yogyakarta: Gadjah Mada University Press.Kartasasmita, G. (1997). Pemberdayaan masyarakat konsep pembangunan yang berakar pada masyarakat. Bandung: Institut Teknologi Bandung.Hanifah, R. (2017). Pengaruh pengetahuan kewirausahaan dan keterampilan wirausaha terhadap keberhasilan usaha Sentra Wajit Cililin di Kecamatan Cililin Kabupaten Bandung Barat. Bandung. Skripsi tidak diterbitkan. Bandung: Unikom.Suryana. (2011). Kewirausahaan. Jakarta: Salemba Empat. Susilo, A. (2016). Model pemberdayaan masyarakat perspektif Islam. Falah: Jurnal Ekonomi Syariah, 1(2). DOI: https://doi.org/10.22219/jes.v1i2.3681Sany, Ulfi Putra. (2019). Prinsip-prinsip pemberdayaan masyarakat  dalam perspektif al-qur’an. Jurnal Ilmu Dakwah, 39(1), 32-44.Lexy J. Moleong. (2005). Metodologi penelitian kualitatif. Bandung: Remaja Rosdakarya.Nazir, Moh. (1998). Metode penelitian. Jakarta: Ghalia Indonesia.